Neurodisability care in the time of COVID‐19. (16th May 2022) - Arichi, Tomoki; Cadwgan, Jill; McDonald, Aoife; Patel, Anita; Turner, Susie; Barkey, Sinead; Lumsden, Daniel E.; Fairhurst, Charlie
Abstract: Background: The COVID‐19 pandemic resulted in an unprecedented societal and healthcare global crisis. Associated changes in regular healthcare provision and lifestyle through societal lockdown are likely to have affected clinical management and well‐being of children/young people with neurodisability, who often require complex packages of multidisciplinary care. Methods: We surveyed 108 families of children/young people with severe physical neurodisability and multiple comorbidities to understand how the pandemic had affected acute clinical status, routine healthcare provision, schooling and family mental and social well‐being. Results: A significant proportion of families reported missing hospital appointments and routine therapy, with subsequent worsening of symptoms and function. Families additionally described worsening stress and anxiety during the pandemic, regardless of their baseline level of socio‐economic deprivation. Conclusion: This highlights the profound effect of the COVID‐19 pandemic on health and function in young people with severe neurodisabilities and emphasizes the clear need to better understand how to support this vulnerable population moving forwards.